2014
DOI: 10.2174/1874088x01408010099
|View full text |Cite
|
Sign up to set email alerts
|

Process and Structure of Electromagnetic Shielding Plywood Composite Laminated with Carbon Fiber Paper

Abstract: Carbon fiber paper (CFP), a type of flexible planer electromagnetic shielding material with thin thickness, low density, and good adhesion property and permeability, was laminated with wood veneer to produce a plywood composite with good shielding effectiveness (SE). It was found that a hot-press pressure of 1.2 MPa and a double-sized adhesive concentration of 380 g/m 2 were most appropriate for the production of CFP plywood composites. SE of plywood composite laminated with single layer CFP was better than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Carbon fiber paper (CFP) is a thin-layer shielding material characterised by low density and good adhesion and permeability. This type of absorber was used to produce plywood characterised by good shielding effectiveness [37]. In the latter study, the optimal plywood production parameters were found to be pressing pressure of 1.2 MPa, temperature of 110 ± 5 • C and glue quantity of 380 g/m 2 .…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…Carbon fiber paper (CFP) is a thin-layer shielding material characterised by low density and good adhesion and permeability. This type of absorber was used to produce plywood characterised by good shielding effectiveness [37]. In the latter study, the optimal plywood production parameters were found to be pressing pressure of 1.2 MPa, temperature of 110 ± 5 • C and glue quantity of 380 g/m 2 .…”
Section: Figurementioning
confidence: 98%
“…In the frequency range from 30 MHz to 1 GHz an absorption level of over 30 dB was reached. Thus, CFP is a promising material for the industrial production of wood composites characterised by high shielding effectiveness [37].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, for the development of integrally conductive filled-type wood-based electromagnetic shielding composite with good attenuation performance, metal membrane (Lu et al 2011), metal powders (Liu and Fu 2009), metal mesh (Zhang et al 2004;Liu et al 2010;Su et al 2013), carbon black, carbon fiber (Hou et al 2015), or plated carbon fiber , carbon fiber paper (Yuan et al 2014), and even mineral powder with excellent electromagnetic properties (Su et al 2012) can be mixed or laminated with wood material to manufacture wood composites with high conductivity and high shielding effectiveness. Wood-based electromagnetic shielding composites have excellent characteristics, but also some limitations, such as high density of the composite with metal filler, complicated construction, and the fact that the texture is too hard to mold.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the methods of increase of the adhesive strength of the laminated wood using intensive technologies (for example, by influence of the electric and magnetic fields, ultrasound, etc.) represent particular scientific and practical interest [3][4].…”
mentioning
confidence: 99%